Learning management system as a necessary element of blended learning - O. V. Andryushkova; M. A. Gorbunov; A. V. Kozlova (Открытое образование (Москва))
The objective of the given work was to study approaches to the choice of software platforms for supporting distance, blended and e-learning. The article presents brief information about the evolution of e-learning systems, and the explanation is given of using the term “blended learning” in case of applying it. The results of comparative analysis are given for systems of managing content and education process exemplified by Moodle 3.2 and DiSpace 2.0, the latter of which is an updated version of a software platform developed by Novosibirsk State Technical University. The following characteristics of e-learning systems were studied: functionalities of modules and subsystems; terms of authorization, installation and support; interface convenience and other parameters. The results are given of polling students about evaluating the indicators of the quality of DiSpace 2.0 e-learning environment (interface friendliness, communication convenience, functional completeness) and electronic educational-methodical complex (availability, content completeness, presentation convenience, involvement in the educational process, topicality). It is pointed in the conclusion, that regardless of the particular learning management system, it should meet the main criteria imposed to basic platforms: openness, expendability, stability, documented nature, and constant development.